Penerapan Metode Pembelajaran Kooperatif Pada Siswa Di MIN 12 Nagan Raya - Hayatunnida, Jihan (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2021)
Cooperative learning method is a form of learning that focuses on the process or activities of working together in carrying out learning activities with groups. The purpose of this study is to describe the cooperative learning method at MIN 12 Nagan Raya. This study uses a qualitative method with a descriptive approach, namely observation, interviews, documentation. The subjects in this study were grade 6 teachers at MIN 12 Nagan Raya. Based on the results of the study, it was found that: 1) The application of cooperative learning methods at MIN 12 Nagan Raya had implemented this model of learning methods. in accordance with the indicators of the characteristics of the cooperative learning method proposed by Isjoni. 2) Teachers at MIN 12 Nagan Raya also use cooperative learning methods according to 20 cooperative learning models, only at MIN 12 Nagan Raya teachers only use ten learning models. 3) Strengths and weaknesses in the cooperative learning method at MIN 12 Nagan Raya, one of which can improve student achievement, this is what teachers really feel when this learning model has been used in the classroom and outside the classroom. Then for the shortcomings of this learning method, the teacher of MIN 12 Nagan Raya said the shortcomings were not too many, only a few points, such as not all teachers understand the cooperative learning model, then the shortcomings can be corrected by the teacher.